Kepemimpinan Transformasional Atasan Mendorong Komitmen Afektif Karyawan Ritel - Erlina Sari Siregar; Diny Atrizka; Ikbar Pratama (Universitas Medan Area, 2023)
A company really needs organizational commitment, that is, employees have a sense of trust in the company, are loyal, and participate or contribute to achieving company goals. Likewise in retail industry, namely products that are produced and distributed in large and mass quantities to be consumed by final consumers in small quantities according to the needs of these consumers. Retail companies seek to improve their human resources to foster the organizational commitment of their employees. Human resources are the most valuable asset in an organization. Aware of the importance of human resources as the industry's main capital asset, it is a concern for the retail industry management by providing training to strengthen leadership in the organizational structure. One form of leadership training needed to emulate employees is through transformational leadership. Transformational leadership training is carried out to stimulate employee affective commitment